2013
DOI: 10.1080/09603123.2012.733939
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of viableAscarissp. and other helminth eggs in sewage sludge

Abstract: Some epidemiologic studies conducted in developing countries demonstrated a high incidence of enteroparasites, Ascaris sp. being the most prevalent. Therefore, the use of sewage sludge in agriculture may pose risks to human health. In order to protect public health, a Brazilian regulation has established standards regarding its use in rural areas. The objective of this study was to quantify Ascaris sp. and other helminth eggs in sewage sludge from five wastewater treatment plants from a dense metropolitan regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Due to the higher prevalence rate, and ability to produce a higher number of ova each day by a female (Bethony et al, 2006;Brooker et al, 2006;Knopp et al, 2012) Dicrocoelium dendriticum have also been reported to be present in wastewater and sludge (Gaspard and Schwartzbrod, 2003;Mahvi and Kia, 2006;Do et al, 2007;Wichuk and McCartney, 2007;Jimenez et al, 2007;Ben Ayed et al, 2009;Kelessidis and Stasinakis, 2012;Bastos et al, 2013;Sharafi et al, 2012;Hajjami et al, 2012;Konate et al, 2013a;Konate et al, 2013b). Commonly detected helminth ova and larvae in the wastewater and sludge around the world, their mode of transmission and the infective stage are presented in The numbers of STHs ova in raw wastewater can be as high as 10 3 per liter depending upon the rate of infection in the community (Gaspard and Schwartzbord, 2003;Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013). Climatic conditions such as temperature, rainfall, relative humidity can also influence the numbers of ova and larvae in the wastewater and sludge (Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013).…”
Section: Prevalence Of Helminths In Wastewater and Sludgementioning
confidence: 99%
See 4 more Smart Citations
“…Due to the higher prevalence rate, and ability to produce a higher number of ova each day by a female (Bethony et al, 2006;Brooker et al, 2006;Knopp et al, 2012) Dicrocoelium dendriticum have also been reported to be present in wastewater and sludge (Gaspard and Schwartzbrod, 2003;Mahvi and Kia, 2006;Do et al, 2007;Wichuk and McCartney, 2007;Jimenez et al, 2007;Ben Ayed et al, 2009;Kelessidis and Stasinakis, 2012;Bastos et al, 2013;Sharafi et al, 2012;Hajjami et al, 2012;Konate et al, 2013a;Konate et al, 2013b). Commonly detected helminth ova and larvae in the wastewater and sludge around the world, their mode of transmission and the infective stage are presented in The numbers of STHs ova in raw wastewater can be as high as 10 3 per liter depending upon the rate of infection in the community (Gaspard and Schwartzbord, 2003;Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013). Climatic conditions such as temperature, rainfall, relative humidity can also influence the numbers of ova and larvae in the wastewater and sludge (Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013).…”
Section: Prevalence Of Helminths In Wastewater and Sludgementioning
confidence: 99%
“…Commonly detected helminth ova and larvae in the wastewater and sludge around the world, their mode of transmission and the infective stage are presented in The numbers of STHs ova in raw wastewater can be as high as 10 3 per liter depending upon the rate of infection in the community (Gaspard and Schwartzbord, 2003;Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013). Climatic conditions such as temperature, rainfall, relative humidity can also influence the numbers of ova and larvae in the wastewater and sludge (Sharafi et al, 2012;Hajjami et al, 2012;Bastos et al, 2013). This could be due to the fact that, STHs ova are known to develop faster at a temperature between 28-32ºC (Seamster, 1950;Beer, 1976;Smith and Schad, 1989;Brooker et al, 2006).…”
Section: Prevalence Of Helminths In Wastewater and Sludgementioning
confidence: 99%
See 3 more Smart Citations